Analisis Optimalisasi Modal Kerja Industri Tempe Skala Kecil Malang - Agni Prajna Yadi; Andik Pratama; Iroh Maharani (STEKOM PRESS, 2023)
This research aims to enhance the productivity and profitability of the small-scale tempe industry in Malang City through the determination and utilization of optimal working capital. Effective management of working capital is crucial for businesses, particularly in relation to sales growth and the need for immediate and close funding of current assets. However, many tempe industries have yet to analyze their working capital requirements, hence this study is expected to contribute valuable insights for the relevant industry to develop their business. The average balance method and the cash inflow-outflow method were employed in this research to determine the required amount of working capital. The sensitivity analysis conducted on Pak Didiek Karim's tempe industry showed that a decrease in production capacity of up to 80% and an increase of soybean up to 60% is still profitable, but an increase in soybean prices can negatively impact profitability. Overall, this research provides a clear overview of the working capital requirements for small-scale tempe industries in Malang City.